The Impact of Urbanization on Economic Growth in Gauteng Province, South Africa - Jacobs, Sarah; David, Oladipo Olalekan; Wyk, Abigail Stiglingh-Van (International Journal of Economics and Financial Issues, 2023)
The apartheid legacy molded urbanization changes in South Africa. Post-1994 people were free to migrate to areas with greater economic activities (increased socio-economic opportunities) subsequently, the genesis of migration. Majority of the people aimed for Gauteng Province which is considered the economic hub of the country and a magnet of opportunities. This study looked at the history of Gauteng- primarily the economic position in conjunction with economic theories. This quantitative research investigated the relationship between economic growth and urbanization in the Gauteng Province. Granger causality tests were used to ascertain the relationship used in the research and the study focused on the period 1997 to 2020, using quarterly data. From the study, it was established that there is a unidirectional causality running from economic growth and employment in Gauteng- meaning that an increase in economic growth enables more jobs to be created, leading to migration of people to the province. The paper also found no causal relationship between population and economic growth- meaning that population increase does not have any effect on economic growth. People seek to progress out of poverty, primarily to an urban lifestyle to leverage socio-economic benefits- grow skills and knowledge by accessing public services such as education, and infrastructure mainly available in urbanized areas. The paper recommends for the government redefine urbanization policy to manage rapid migration. Failure to do so will lead to infrastructure ( housing, water, and electricity) and employment challenges within the province.